Antisense Oligonucleotide Inhibition of MicroRNA-494 Halts Atherosclerotic Plaque Progression and Promotes Plaque Stabilization - Eva van Ingen; Amanda C. Foks; Mara J. Kröner; Johan Kuiper; Paul H.A. Quax; Ilze Bot; Anne Yaël Nossent (Elsevier, 2019)
We have previously shown that third-generation antisense (3GA) inhibition of 14q32 microRNA (miRNA)-494 reduced early development of atherosclerosis. However, patients at risk of atherosclerotic complications generally present with advanced and unstable lesions. Here, we administered 3GAs against 14q32 miRNA-494 (3GA-494), miRNA-329 (3GA-329), or a control (3GA-ctrl) to mice with advanced atherosclerosis. Atherosclerotic plaque formation in LDLr−/− mice was induced by a 10-week high-fat diet and simultaneous carotid artery collar placement. Parallel to 3GA-treatment, hyperlipidemia was normalized by a diet switch to regular chow for an additional 5 weeks. We show that, even though plasma cholesterol levels were normalized after diet switch, carotid artery plaque progression continued in 3GA-ctrl mice. However, treatment with 3GA-494 and, in part, 3GA-329 halted plaque progression. Furthermore, in the aortic root, intra-plaque collagen content was increased in 3GA-494 mice, accompanied by a reduction in the intra-plaque macrophage content. Pro-atherogenic cells in the circulation, including inflammatory Ly6Chi monocytes, neutrophils, and blood platelets, were decreased upon miRNA-329 and miRNA-494 inhibition. Taken together, treatment with 3GA-494, and in part with 3GA-329, halts atherosclerotic plaque progression and promotes stabilization of advanced lesions, which is highly relevant for human atherosclerosis.